Circulating T cell subsets are associated with clinical outcome of anti-VEGF-based 1st-line treatment of metastatic colorectal cancer patients: a prospective study with focus on primary tumor sidedness - Bencsikova, Beatrix; Budinska, Eva; Selingerova, Iveta; Pilatova, Katerina; Fedorova, Lenka; Greplova, Kristina; Nenutil, Rudolf; Valik, Dalibor; Obermannova, Radka; Sheard, Michael A; Zdrazilova-Dubska, Lenka (BMC cancer, 2019)
BACKGROUND: In a prospective study with long-term follow-up, we analyzed circulating T cell subsets in patients with metastatic colorectal cancer (mCRC) in the context of primary tumor sidedness, KRAS status, and clinical outcome. Our primary goal was to investigate whether baseline levels of circulating T cell subsets serve as a potential biomarker of clinical outcome of mCRC patients treated with an anti-VEGF-based regimen. METHODS: The study group consisted of 36 patients with colorectal adenocarcinoma who started first-line chemotherapy with bevacizumab for metastatic disease. We quantified T cell subsets including Tregs and CD8+ T cells in the peripheral blood prior to therapy initiation. Clinical outcome was evaluated as progression-free survival (PFS), overall survival (OS), and objective response rate (ORR). RESULTS: 1) mCRC patients with KRAS wt tumors had higher proportions of circulating CD8+ cytotoxic T cells among all T cells but also higher measures of T regulatory (Treg) cells such as absolute count and a higher proportion of Tregs in the CD4+ subset. 2) A low proportion of circulating Tregs among CD4+ cells, and a high CD8:Treg ratio at initiation of VEGF-targeting therapy, were associated with favorable clinical outcome. 3) In a subset of patients with primarily right-sided mCRC, superior PFS and OS were observed when the CD8:Treg ratio was high. CONCLUSIONS: The baseline level of circulating immune cells predicts clinical outcome of 1st-line treatment with the anti-VEGF angio/immunomodulatory agent bevacizumab. Circulating immune biomarkers, namely the CD8:Treg ratio, identified patients in the right-sided mCRC subgroup with favorable outcome following treatment with 1st-line anti-VEGF treatment.
Keywords: regulační T-lymfocyty; Colorectal Neoplasms; doba přežití bez progrese choroby; Bevacizumab; mužské pohlaví; míra přežití; Male; senioři; senioři nad 80 let; protoonkogenní proteiny p21(ras); Female; Humans; Regulatory T cells; cytotoxické T-lymfocyty; T-Lymphocytes, Regulatory; následné studie; lidé; metastázy nádorů; Follow-Up Studies; Biomarkers, Tumor; Lymphocyte Count; Prospective Studies; Middle Aged; nádorové biomarkery; ženské pohlaví; bevacizumab; lidé středního věku; Metastatic colorectal cancer; T-Lymphocytes, Cytotoxic; Adenocarcinoma; Progression-Free Survival; Aged, 80 and over; Vascular Endothelial Growth Factor A; vaskulární endoteliální růstový faktor A; Anti-VEGF; Primary colorectal carcinoma sidedness; počet lymfocytů; kolorektální nádory; prospektivní studie; Angiogenesis Inhibitors; inhibitory angiogeneze; dospělí; Neoplasm Metastasis; Adult; adenokarcinom; Survival Rate; Antitumor immune response; T cell subsets; Proto-Oncogene Proteins p21(ras); Aged